Early mortality in prophylactic implantable cardioverter-defibrillator recipients: development and validation of a clinical risk score. Issue 1 (4th August 2013) - Kraaier, Karin; Scholten, Marcoen F.; Tijssen, Jan G.P.; Theuns, Dominic A.M.J.; Jordaens, Luc J.L.M.; Wilde, Arthur A.M.; van Dessel, Pascal F.H.M.
Abstract: Aims: To reduce sudden cardiac death, implantable cardioverter-defibrillators (ICDs) are indicated in patients with ischaemic and non-ischaemic dilated cardiomyopathy and a left ventricular ejection fraction (LVEF) ≤35%. Current guidelines do not recommend device therapy in patients with a life expectancy <1 year since benefit in these patients is low. In this study, we evaluated the incidence and predictors of early mortality (<1 year after implantation) in a consecutive primary prevention population. Methods and results: Analysis was performed on a prediction and validation cohort. The primary endpoint was all-cause mortality at 1 year. The prediction cohort comprised 861 prophylactic ICD recipients with ischaemic cardiomyopathy or dilated cardiomyopathy from the Academic Medical Center (Amsterdam) and Thorax Center Twente (Enschede). Detailed clinical data were collected. After multivariate analysis, a risk score was developed based on age ≥75 years, LVEF ≤ 20%, history of atrial fibrillation, and estimated glomerular filtration rate (eGFR) ≤30 mL/min/1.73 m 2 . Using these predictors, a low (≤1 factor), intermediate (2 factors), and high (≥3 factors) risk group could be identified with 1-year mortality of, respectively, 3.4, 10.9, and 38.9% ( P < 0.01). Afterwards, the risk score was validated in 706 primary prevention patients from the Erasmus Medical Center (Rotterdam). One-year mortality was, respectively, 2.5, 13.2, and 46.3% (all P < 0.01). Conclusion: A simple risk score based on age, LVEF, eGFR, and atrial fibrillation can identify patients at low, intermediate, and high risk for early mortality after ICD implantation. This may be helpful in the risk assessment of ICD candidates.